The Council of Europe should not reaffirm the ban on germline genome editing in humans. (6th October 2017) - Sykora, Peter; Caplan, Arthur
Abstract : The Council of Europe plans to urge member states to sign and ratify the Oviedo Convention that would ban all inheritable modifications of the human germline. Such a policy would prevent research to develop new therapeutic options for inheritable diseases in Europe and is in sharp contrast to international developments.